Epidemiologic Profile of Thyroid Disorders in a Tertiary Care Hospital, a Five Years Analysis - Asma Nafisa, Nadeem Ikram, Soffia Khursheed, Rabia Anjum, Naeem Akhtar, (Journal of Rawalpindi Medical College, 2021)
Background: Thyroid disorders are commonly encountered endocrine ailments in clinical practice. Objective: To determine the trends and frequency of thyroid disorders in patients presented for thyroid dysfunction at the department of Pathology Benazir Bhutto hospital Rawalpindi Study Design: Cross-sectional retrospective study. Materials and Methods: Patients who underwent thyroid function tests were enrolled in the study Thyroid function tests were performed on a fully automated Chemistry Analyzer. Graph Pad Prism version 7 and SPSS version 25 were used for statistical analysis of the data. Results: Out of 2856 patients, 81.9% were females and 18.1% were males. The mean age of the participants was 38.12 ± 14.51 years and the median was 35(13-96). Overall, 1951 (68.3%) of the subjects were euthyroid, 343(12.0%) had subclinical hyperthyroidism, 200 (7.0%) had subclinical hypothyroidism, 192(6.7%) had overt hyperthyroidism and 168 (5.9%) had overt hypothyroidism. Females have a significantly high percentage of thyroid disorders as compared to males(χ2 =0.976 p =0.027). The major age group 798(27.9 %) tested for thyroid dysfunction suspicion was 24 to 33 years followed by 34-43 (22.9%). Conclusions: The thyroid dysfunction prevalence was higher in females than males. An upward trend in the frequency of thyroid dysfunction was observed with increasing age. Subclinical hyperthyroidism was the commonest abnormality observed. A steep rise in subclinical hyperthyroidism may be attributed to the high intake of iodized salt.